Correction to: Primary, Secondary, and Tertiary Effects of Carbohydrate Ingestion During Exercise - Ian Rollo; Javier T. Gonzalez; Cas J. Fuchs; Luc J. C. van Loon; Clyde Williams (Sports Medicine, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s40279-021-01489-8